Pengaruh Pemberian Madu Terhadap Pengeluaran Asi Pada Ibu Pasca Salin - Yuliaswati, Enny; Kamidah, K; Kusumadewi, Rita Riyanti (Indonesian Journal on Medical Science, 2024)
One common obstacle during lactation is the delayed onset of breast milk production. To address the issue of delayed breast milk secretion, a potential solution is administering honey as a stimulus to facilitate timely milk production. This research aims to assess the effectiveness of honey supplementation in promoting breast milk secretion among postpartum mothers at Klinik Hidayah Baki Sukoharjo. The study adopts a Quasi-Experimental design with one control group and one case group. Consecutive Sampling is employed, with a sample size of 40 respondents meeting the inclusion criteria. The statistical test utilized is the Mann-Whitney test. The research findings indicate that breast milk secretion is smoother in the experimental group, with an average on the 4th day, compared to the control group with an average on the 7th day. Therefore, the use of honey appears to expedite breast milk secretion in postpartum mothers. The p-value is 0.010 (p < 0.05), signifying a significant difference in breast milk secretion between the experimental and control groups. Based on these results, it can be concluded that honey supplementation is effective in accelerating breast milk secretion in postpartum mothers.